Students Team Achievement Division (STAD): Model Pembelajaran Kooperatif untuk Meningkatkan Kerja Sama Peserta Didik - Arif Dwihantoro (Pusat Studi Pengembangan Pembelajaran Matematika Sekolah UIN Sunan Kalijaga Yogyakarta Jl. Marsda Adisucipto, Yogyakarta 55281, 2021)
The research aimed to increase students' cooperation skills and to describe mathematics learning quality through cooperative learning models, types Students Team Achievement Division (STAD). This research is a classroom action research using model of Kemmis Taggart. The subject is 11 grades students of Mathematics and Natural Science 3 in 1 Wates Senior High School. The findings indicated that the learning model, style Students Team Achievement Division (STAD), could improve students' cooperation skill. The excellent implementation is shown by an improvement in the percentage of student cooperation in mathematics instruction, namely from the results of the first cycle, the average performance of cooperation is 67.8% of students in the high and very high category and an increase in the second cycle by 82.2% of students in the high and very high category. The results of observations of the implementation of mathematics learning using cooperative learning model, type Students Team Achievement Division (STAD), in cycle I revealed a percentage of 91%, which increased to 96% in cycle II.